Manajemen Implementasi Hasil Diklat Berjenjang Dasar Paud dalam Peningkatan Kualitas Pembelajaran - Sriastuti Sriastuti; Juhri AM; Fatqul Hajar Aswad (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
The management of the implementation of Basic Level PAUD Tiered Training results is a crucial factor in improving the quality of early childhood learning. This study aims to describe and analyze the management of the implementation of PAUD Tiered Training outcomes in improving learning quality at PAUD institutions in Gisting District, Tanggamus Regency. The study focused on four management functions: planning, organizing, actuating, and controlling, as well as identifying inhibiting factors and the output of implementation. A qualitative approach with a case study design was employed. Data were collected through interviews, observations, and documentation, and analyzed using the Miles & Huberman interactive model. The findings revealed that implementation management was conducted systematically, though constrained by time, funding, and facilities. The training implementation resulted in improved instructional tools and learning processes. This research supports the development of continuous professional training policies for early childhood educators.